Indegenous People’s Participation in the Election of the Mayor and Deputy Mayor of Ternate City - Nam Rumkel; Fatma Faisal; Andika Adhyaksa (Universitas Islam Sultan Agung, 2026)
This study aims to determine the participation of indigenous peoples in the election of the Mayor and Deputy Mayor of Ternate City. There is an interesting phenomenon to examine regarding the participation of indigenous peoples in regional head elections and the causes of political involvement in the implementation of regional head elections. The method used in this study is empirical research, which is a legal research method that serves to observe the law in its real sense, analyze and examine the workings of the law within the community. The empirical research method also includes research on legal identification and research on legal effectiveness. To support the substance of this research, it focuses on the use of primary data obtained directly from respondents and secondary data from books, journals, laws and regulations, and all documents relevant to the research. The data was obtained using data collection techniques such as interviews and documentation, which were then analyzed using qualitative descriptive analysis methods. The results of this study show that the implementation of direct regional head elections is an important momentum for the development of a more democratic local political system. Through direct regional elections, many hopes are pinned on improving the welfare of the people in the regions, as regional heads become closer to the people because they obtain political legitimacy directly from the people. Direct regional elections are considered by many parties to be an important step forward that can be achieved by the Indonesian nation in the current era of transition. “Direct” refers to, among other things: First, constitutional recognition of the people's right as holders of sovereignty; second, the institutionalization of the people's substantial role as subjects of law; and third, the hoped-for creation of macro and micro political balance in state affairs, particularly between the executive and legislative branches. Voter participation in regional elections does not happen by itself. In addition to the role of election organizers in conducting socialization, it is also due to support from other parties, namely the role of indigenous peoples. The participation of indigenous peoples in encouraging the community to participate in regional elections is very strategic in ensuring the success of the elections.